American foreign policy : Studies in intellectual history - Drolet, Jean-François; Dunkerley, James (Manchester International Relations, 2017)
This book offers a nuanced and multifaceted collection of essays covering a wide range of concerns, concepts, presidential doctrines, and rationalities of government thought to have marked America's engagement with the world during this period. The collection is organised chronologically and looks at the work of intellectuals who have written both in support and critically about US foreign policy in various geographical and historical contexts. This includes Andrew Carnegie, Carl Schmitt, Hans Morgenthau, George Kennan, Samuel Huntington, Paul Wolfowitz and many other such thinkers and practitioners who have contributed in shaping the ways in which we have come to think of US foreign policy over the years. The book will be of significant interest to students and academics within the fields of US foreign policy analysis, international relations and intellectual history.